Production Technology and Efficiency of Farmer’s Dairy Entreprises (A Case Study in the Regency of Bogor, Boyolali, and Pasuruan) - Fuah A.M; D. J. Setyono; B. P. Purwanto; A. A. Fuah (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
During for the past 10 years, milk production in Indonesia has been on the increase of approximately 70% (FAO, 2002), but it can only meet 30% of domestic needs for milk. The remaining 70% is still imported, mostly from Australia and New Zealand. Milk production in Indonesia is expected to increase to achieve an average of 15-20 liters/cow/day. It is necessary to analyze dairy enterprises to assess its feasibility. The objectives of this study were: (1) to evaluate production technology of small holder dairy farm in West Java, Central Java and East Java; (2) to analyze the efficiency of the existing dairy farming. Twenty farmers from each localities with ownership less than or equal to 10 cows, consisted of small (<4 cows), medium (4-6 cows), and large (> 6 cows) scales were interviewed on their businesses. Economic analysis on net profit indicated by BC-Ratio, and IRR values. The dairy farming in West Java, Central Java and East Java was carried out traditionally without technological diversification, the main products were pasteurised fresh milk. Milk production was low (10 liters/cow/day). Net income of Rp 1,521,820/m/farmers, BC-Ratio 1.32, and IRR 17% indicated a low result. Improving cows ownership should be in line with the improved management and technology application.